Desain Primer In Silico Untuk Analisis Expresi Gen Osteopontin (OPN) Sebagai Penanda Kesuburan Pada Kambing Jantan (Capra hircus) - Sukoco, Hendro; Suriansyah, Suriansyah; Salmin, Salmin; Cahyani, Annisa Putri; Andanawari , Suci; Akbarrizki , Muzizat; Siswanto, Ferbian Milas (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
This study aimed to design a pair of primers for analyzing OPN gene expression as a fertility marker in male goats (Capra hircus). The research method employed was an in silico molecular study based on bioinformatics. Nucleotide data were retrieved from the NCBI database using the code NM_001285667.1. The data obtained were processed using Primer-Blast on the NCBI site to identify candidate primers. These candidate primers were subsequently analyzed for secondary structure and primer dimer formation using the Sigma-Aldrich OligoEvaluator.The designed primers were further analyzed for their specifications and sequence similarity with the nucleotide database available on the NCBI site using Primer-Blast and Nucleotide-Blast. The results revealed one pair of primers with ideal criteria: the forward primer 5'-ACCCTCCCGAGTAAGTCCAA-3' and the reverse primer 5'-AGTCCTCCTCTGTGGCATCT-3', capable of amplifying the OPN gene region with a product length of 325 bp. In silico performance tests also demonstrated that the primers could specifically detect the OPN gene in Capra hircus. The primer design for detecting OPN expression is expected to aid in predicting fertility levels in male goats (Capra hircus), thereby enhancing the reproductive efficiency of these livestock.